Electrochemical Investigation of 1-Ethyl-3-methylimidazolium Bromide and Tetrafluoroborate Mixture at Bi(111) Electrode Interface. Issue 9 (23rd June 2016) - Siimenson, Carolin; Lembinen, Meeri; Oll, Ove; Läll, Laura; Tarkanovskaja, Marta; Ivaništšev, Vladislav; Siinor, Liis; Thomberg, Thomas; Lust, Karmen; Lust, Enn
Abstract : Electrochemical characterization of the interface between Bi(111) surface and ionic liquid mixtures of 1-ethyl-3-methylimidazolium tetrafluoroborate with 1-ethyl-3-methylimidazolium bromide (EMImBF4 + x % EMImBr) has been evaluated by using the electrochemical impedance spectroscopy, cyclic voltammetry methods and density functional theory calculations. Dependence of the experimental data on the bromide concentration and on the electrode potential has been analyzed. Comparison of adsorption data with Bi(111) | EMImBF4 + x % EMImI interface shows that adsorption activity of halide ions from EMImBF4 follows a similar trend as from the aqueous and organic electrolyte solutions. The adsorption activity of anions increases in order Cl − < Br − < I −, despite the fact that the solvation properties of relevant media are significantly different. We discuss this trend in the light of a possible application of the RTIL mixtures as an electrolyte for electrochemical energy storage devices like supercapacitors.